Generation of Photon Orbital Angular Momentum and Its Application in Space Division Multiplexing - Temitope M. Olaleye; Paulo A. Ribeiro; Maria Raposo (Photonics, 2023)
In the last three decades, light’s orbital angular momentum (OAM) has been of great interest because it has unique characteristics that make it sought after in many research fields, especially in optical communications. To address the exponentially increasing demands for higher data rates and capacity in optical communication systems, OAM has emerged as an additional degree of freedom for multiplexing and transmitting multiple independent data streams within a single spatial mode using the spatial division multiplexing (SDM) technology. Innumerable research findings have proven to scale up the channel capacity of communication links by a very high order of magnitude, allowing it to circumvent the reaching of optical fiber’s non-linear Shannon limit. This review paper provides a background and overview of OAM beams, covering the fundamental concepts, the various OAM generators, and the recent experimental and commercial applications of the OAM-SDM multiplexing technique in optical communications.